Cryptospatial Coordinate using the RPCA Based on a Point in Polygon Test for Cultural Heritage Tourism - Achmad Teguh Wibowo; MY Teguh Sulistyono; Mochamad Hariadi (Communications - Scientific letters of the University of Zilina, 2020)
This research was aimed to enhance the cryptospatial with geospatial blockchain based on a point in polygon test. Ripple Protocol Consensus Algorithm (RPCA) was used for developing a blockchain. The steps taken include: (1) Data from the surveyors were entered using application connected to the transaction set; (2) The transaction set sent data to the transaction proposal; (3) The transaction proposal will distribute to every connected validating of nodes for executing the smart contract with the point in a polygon test method; (4) If the process succeeded with the maximum fault tolerance of 20%, then the node records a new chain to the ledger. This method is faster than Practical Byzantine Fault Tolerance (PBFT) blockchain for approximately 26% to add a new chain in the ledger and for 52% to decrypt the blockchain with a mobile device. The result of this process is a cryptospatial coordinate for the cultural heritage tourism.